Home bias in the global portfolio investment of selected OIC countries/ Nura Lina Md Elias, Syed Musa Al-Habshi and Razali Haron - Md Elias, Nura Lina; Al-Habshi, Syed Musa; Haron, Razali (Universiti Teknologi MARA Selangor, 2022)
Home bias reflects the propensity of investors to allocate their portfolio substantially in domestic market. The existence of home bias offers a new discovery that enables for a comprehensive and robust investigation of such phenomenon. Therefore, the main agenda of this research is to examine the determinants of home bias in the global portfolio investment of selected OIC countries. An unbalanced bilateral panel data of 12 OIC countries’ outward equity investment in 74 host countries from year 2001 to 2016 was analysed. System Generalized Method of Moments (GMM) estimator was employed to determine the factors influencing home bias. The findings show that home bias can be explained by factors related to institutional quality, familiarity, and global financial crisis. The relative factors introduced in the current study significantly explained the existence of home bias phenomenon. Summative findings indicate that home bias may discourage global portfolio investment, but there is a tendency of over-investment in MENA region based on geographical preferences. This study has a significant implication to investors, fund managers and regulators of the OIC countries. Investors and fund managers in OIC countries should be aware of the existence of home bias in their global portfolio that may potentially reduce the benefits of optimal diversification. It is a call for policy makers in the OIC countries to convince their local investors that international portfolio diversifications are able to minimize portfolio’s risk and eventually increase the investment returns.